Regulation of Carbohydrate Metabolism by Trehalose-6-Phosphate Synthase 3 in the Brown Planthopper, Nilaparvata lugens - Wang, Sha-Sha; Li, Guo-Yong; Liu, Yong-Kang; Luo, Yu-Jia; Xu, Cai-Di; Li, Can; Tang, Bin (Frontiers in Physiology, 2020)
Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) is one of the pests that harm rice. In this paper, a new trehalose-6-phosphate synthase gene, TPS3, was identified by transcriptome sequencing and gene cloning. To explore its role in the energy metabolism of N. lugens we examined the carbohydrate contents at different stages of development, the tissue expression of TPS, and some physiological and biochemical indicators by injecting dsTPS3 and dsTPSs (a proportional mixture of dsTPS1, dsTPS2, and dsTPS3). The glucose content at the fifth instar was significantly higher than that in the fourth instar and the adult stages. The trehalose and glycogen contents before molting were higher than those after molting. TPS1, TPS2, and TPS3 were expressed in the head, leg, wing bud, and cuticle, with the highest expression in the wing bud. In addition, compared with the control group, the glucose content increased significantly at 48 h after RNA interference, and the trehalose content was significantly decreased after 72 h. qRT-PCR showed that the expression level of UGPase decreased significantly at 48 h after injection, whereas GS expression was increased significantly at 48 h after injecting dsTPS3. After dsTPS injection, the expression levels of PPGM2, UGPase, GP, and GS were significantly increased at 72 h. After interfering with the expression of TPS3 gene alone, UGPase expression decreased significantly at 48 h, and GS expression increased significantly at 72 h. Finally, combined with the digital gene expression and pathway analysis, 1439 and 1346 genes were upregulated, and 2127 and 1927 genes were downregulated in the dsTPS3 and dsTPSs groups, respectively. The function of most differential genes was concentrated in sugar metabolism, lipid metabolism, and amino acid metabolism. The results indicated that TPS3 plays a key role in the energy metabolism of N. lugens and confirmed that TPS3 is a feasible target gene for RNA interference in N. lugens. Simultaneously, they provide a theoretical basis for the development and utilization of TPS3 to control pests.